SOSIALISASI PENDIDIKAN PANCASILA DAN KEWARGANEGARAAN: MEMBANGUN KESADARAN BERBANGSA DI KALANGAN PELAJAR DESA GANOWO SAUA - Darwin Gaurifa (Universitas Nias Raya, 2024)
This community service initiative aims to build a sense of national awareness among students in Ganowo Saua Village through the socialization of Pancasila values and citizenship education. The activities include workshops, interactive discussions, and social practices that involve active participation from students. The results indicate an improvement in students' knowledge and understanding of Pancasila, as well as an increased sense of love for the homeland and participation in social activities. By involving families and the community, this program is expected to create a broader awareness of the importance of national values. It is hoped that this initiative will produce a responsible and active generation of youth who contribute to society.